Health Plan Design: A Way to Risk Assessment or Risk Avoidance? - A Comparison towards Private Health Insurance Products and Services of Selected Firms in the US and the UK - Wu, Si (2007)
Many observations suggest that the health insurance market rewards those health plans that manage to sell the largest percentage of their product to people who need it the least, and avoid those likely to use it the most. That means health insurers develop health insurance plans in such a way that plans are attractive to the low risk individuals but at the expense of coverage to the high risk type. The strategies that they use are in setting the rates to risk selection and classification, underwriting and utilization management. They also concern with the supply side of service the providers, and monitor the way that they behave to control services utilization and cost. However, the conduct of such strategies are varied in the US and UK due to the different market and regulation environments. So this study uses the method of reviewing the accounts and produce design of ten selected companies in the US and UK, and show the major differences of firm response to health risks. Content analysis is used to categorize plan design into theoretical themes. The study finds that: ÃÂ· The US insureds have experienced more stringent rating standards in obtaining coverage and the premium they pay is higher (than that paid bythe UK insureds) ÃÂ· In the US, lower cost sharing increases the demand for coverage ÃÂ· Better quality of health insurance is delivered in the US market ÃÂ· UK plans rely more on cost sharing ÃÂ· Risk selection is exercised in a lesser extent in the UK ÃÂ· In both countries, consumers are encouraged to use the services provided by in-network providers as consumers who use out-of-network providers are penalised by higher premiums or they may not obtain coverage ÃÂ· More tightened insurer-provider relationship is found in the US